Language and religion as factors of division in the Indian community. Aspects of the South African case - Kahn, Stan (My University, 1975)
Studies of Indians in South Africa have fallen, in the main, into two categories. There have been descriptive works which have stressed the history of the Indian population up to the present time, while on the other hand, there have been works with a strong political flavour. This latter group have focussed on the relationship between the White power elite, and the Indians as a negatively defined minority group. While elements of the latter have not been completely absent in the former group, the focus of this former group has been on less analytical descriptions of the Indian community in South Africa.
African Studies Seminar series. Paper presented October, 1975